Outcomes of Total Laparoscopic Hysterectomy Versus Total Abdominal Hysterectomy with Bilateral Salpingo-Oophorectomy in Endometrial Carcinoma - Viko Duvadilan Wibowo; Febia Erfiandi; Hartanto Bayuaji (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objective: Management of endometrial carcinoma may involve total hysterectomy with bilateral salpingo-oophorectomy (TH-BSO), performed either laparoscopically or via laparotomy. This evaluation is crucial for assessing recovery and determining appropriate follow-up care in patients with endometrial cancer based on the ECOG Performance Status.Methods: This retrospective cohort study examined data from patients who underwent THBSO at Dr. Hasan Sadikin Hospital in 2024. The primary outcome measured was ECOG performance status at one month and six months post-surgery. The analysis was conducted using the Mann-Whitney U test to compare ECOG scores between the laparoscopic and laparotomy groups. Result: Of the 47 patients (28 laparotomies and 19 laparoscopies), the Mann-Whitney U test results for the ECOG score one month postoperatively showed no significant difference between patients who underwent THBSO with laparoscopic and laparotomy techniques (p = 0.921). However, the results of the 6-month postoperative ECOG score test indicated a significant difference between the two groups (p = 0.026), with better outcomes in the laparoscopic group. Conclusion: ECOG performance status after laparoscopy in endometrial cancer cases was better than after laparotomy. AbstrakTujuan: Penatalaksanaan karsinoma endometrium dapat dilakukan dengan histerektomi total disertai salpingo-ooforektomi bilateral, yang dilakukan baik secara laparoskopi maupun melalui laparotomi. Penilaian ini penting untuk mengevaluasi proses pemulihan dan menentukan tata laksana tindak lanjut yang tepat pada pasien kanker endometrium berdasarkan ECOG Performance Status.Metode: Studi kohort retrospektif ini menganalisis data pasien yang menjalani HTSOB di RSUP Dr. Hasan Sadikin pada tahun 2024. Luaran utama yang dinilai adalah ECOG performance status satu bulan dan enam bulan postoperatif. Analisis dilakukan menggunakan uji Mann-Whitney U untuk membandingkan skor ECOG antara kelompok laparoskopi dan laparotomi.Hasil: Dari 47 pasien (28 laparotomi dan 19 laparoskopi), hasil uji Mann-Whitney U terhadap skor ECOG satu bulan postoperatif menunjukkan bahwa tidak terdapat perbedaan bermakna antara pasien yang menjalani HTSOB dengan teknik laparoskopi dan laparotomi (p = 0.921). Sedangkan hasil uji skor ECOG 6 bulan postoperatif menunjukkan bahwa terdapat perbedaan signifikan antara kedua kelompok (p = 0.026), dengan hasil lebih baik pada kelompok laparoskopi.Kesimpulan: ECOG performance status pasca laparoskopi pada kasus kanker endometrium lebih baik daripada laparotomi.